Nonequilibrium quantum transport physics in nanosystems : foundation of computational nonequilibrium physics in nanoscience and nanotechnology - 531394 Buot, Felix A. (Hackensack, NJ. : World Scientific, 2009)
Includes bibliographical references (p. 803-809) and index.